Measuring the healthfulness of food retail stores: variations by store type and neighbourhood deprivation - Black, Christina (BioMed Central, 2014)
BACKGROUND: The consumer nutrition environment has been conceptualised as in-store environmental factors that influence food shopping habits. More healthful in-store environments could be characterised as those which promote healthful food choices such as selling good quality healthy foods or placing them in prominent locations to prompt purchasing. Research measuring the full-range of in-store environmental factors concurrently is limited. PURPOSE: To develop a summary score of ‘healthfulness’ composed of nine in-store factors that influence food shopping behaviour, and to assess this score by store type and neighbourhood deprivation. METHODS: A cross-sectional survey of 601 retail food stores, including supermarkets, grocery stores and convenience stores, was completed in Hampshire, United Kingdom between July 2010 and June 2011. The survey measured nine variables (variety, price, quality, promotions, shelf placement, store placement, nutrition information, healthier alternatives and single fruit sale) to assess the healthfulness of retail food stores on seven healthy and five less healthy foods that are markers of diet quality. Four steps were completed to create nine individual variable scores and another three to create an overall score of healthfulness for each store. RESULTS: Analysis of variance showed strong evidence of a difference in overall healthfulness by store type (p < 0.001). Large and premium supermarkets offered the most healthful shopping environments for consumers. Discount supermarkets, ‘world’, convenience and petrol stores offered less healthful environments to consumers however there was variation across the healthfulness spectrum. No relationship between overall healthfulness and neighbourhood deprivation was observed (p = 0.1). CONCLUSIONS: A new composite measure of nine variables that can influence food choices was developed to provide an overall assessment of the healthfulness of retail food stores. This composite score could be useful in future research to measure the relationship between main food store and quality of diet, and to evaluate the effects of multi-component food environment interventions.